KUMPULAN SOAL BUKU AJAR PLUSPUNKT DEUTSCH SEBAGAI LATIHAN TAMBAHAN KETERAMPILAN MEMBACA BAHASA JERMAN UNTUK SMA KELAS XI SEMESTER II - Aprianti, Ratih (LATERNE, 2017)
In learning a foreign language, the skills of reading is a skill that must be mastered by students. Learner is expected to understand the different types of readings and a series of text that they meet. One of the means of learning German is a textbook. The textbook plays a great role for teachers as well as for learners. For this reason, an analysis is needed in the German language book, namely Pluspunkt Deutsch. In this textbook there are many exercises that increase the learning process. According to Hans – Jürgen Krumm (in Kast and Neuner), exercise is an aspect that can be analyzed by the textbook. The title of this research is "The collection of the tasks of the textbook Pluspunkt Deutsch as additional exercises of the German reading skills for SMA class XI second semesters".                  The problem of this research is "conformity the exercises in Pluspunkt Deutsch with the subject, curriculum contents in 2013 (revised), vocabulary, as well as the form and purpose of the reading skills, which can be applied to class IX second semesters as additional exercises German reading skills". This research uses the revised 2013 curriculum as a reference, which develops the indicators, the theory of the exercise type of Albers and Bolton as well as the purpose of Bolton. These aspects work for the analysis of the reading exercises in research data.                 The results show that there are 3 lessons with the theme of Alltagsleben, with 11 reading exercises. After analyzing compliance with aspects such as topic, curriculum contents, vocabulary, reading exercise type, and purpose of reading, these research results will yield 9 exercises for reading skills. While 2 other exercises do not meet the aspects of the topic of learning. Keywords: Textbook, additional exercises, reading skills